2004
DOI: 10.1021/la0479859
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Nanofiltration Properties of Multilayer Polyelectrolyte Membranes through Variation of Film Composition

Abstract: We report the use of a variety of polyelectrolyte multilayers (PEMs) as selective skins in composite membranes for nanofiltration (NF) and diffusion dialysis. Deposition of PEMs occurs through simple alternating adsorption of polycations and polyanions, and separations can be optimized by varying the constituent polyelectrolytes as well as deposition conditions. In general, the use of polycations and polyanions with lower charge densities allows separation of larger analytes. Depending on the polyelectrolytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 50 publications
3
148
0
Order By: Relevance
“…[28][29][30] Utilizing surface adsorbed polyelectrolyte nanofilms to control substrate diffusion, a more complex microparticle biosensor system based on calcium alginate hydrogel microspheres that contained and an oxygen-quenched ruthenium compound was demonstrated. 9,24,31 In this system, which used glucose as a model analyte, local oxygen levels (internal to the particle) are proportionally reduced through glucose oxidase (GOx)-initiated catalysis (Scheme 1) and tracked through relative changes in ruthenium emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Utilizing surface adsorbed polyelectrolyte nanofilms to control substrate diffusion, a more complex microparticle biosensor system based on calcium alginate hydrogel microspheres that contained and an oxygen-quenched ruthenium compound was demonstrated. 9,24,31 In this system, which used glucose as a model analyte, local oxygen levels (internal to the particle) are proportionally reduced through glucose oxidase (GOx)-initiated catalysis (Scheme 1) and tracked through relative changes in ruthenium emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…The capsule wall represents a semipermeable membrane, as small molecules can diffuse almost freely through the pores [13], whereas large molecules, for example dextran molecules or proteins, cannot pass the capsule walls. The molecular weight cut-off (MWCO) for PSS/PAH is around 200 Da [14]. The MWCO depends on the polymers, and…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%
“…Miller and Bruening showed that, for example, the combination of hyaluronic acid (HA) and chitosan had a MWCO of ≈17,000 Da [14,15]. Due to the semipermeability of the capsule wall a Donnan equilibrium occurs [16], which means that the concentration of ions and molecules inside of the capsules is different of the concentrations outside, also in case of molecules or ions, for which the membrane is permeable.…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%
“…PEM's can provide membranes with antifouling functionalities [11,12,[14][15][16][17][18], as well as act as the separation (skin) layer for NF membranes [19]. Most of the previous studies on PEM based NF membranes, utilized flat sheet membrane supports as reported for example by Bruening et al [20][21][22][23][24][25] and Tieke et al [26,27]. However, the hollow fiber configuration would offer a higher productivity [28,29].…”
Section: Introductionmentioning
confidence: 99%